Reconstruction of Pregnancy Marriage Legality in Indonesia - Ja’far, Kumedi; Nasution, Khoiruddin; Abror, Khoirul; Hermanto, Agus (International Journal of Criminology and Sociology, 2022)
Normatively, the scholars agreed that pregnant women marriage is considered legal, but it must be carried out again after giving birth. There is a renewal of the law relating to the legality of the marriage contract for a pregnant woman. In this case the Indonesian Islamic scholars consider sociological and psychological elements especially the local culture of Indonesian society, but then KHI was a compromising approach to customary law. That compromise is seen from fact happened deviation in teaching of fiqh associated with sociological and psychological factors. Besides, the ultimate goal of permission principle of marrying pregnant woman is to provide a definite law protection to child in the womb, even though that child’s status is outside of marriage